2016
DOI: 10.1021/acscatal.6b01599
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Ynamide Oxidation Strategy for the Preparation of α-Functionalized Amides

Abstract: A Lewis acid-catalyzed alkyne oxidation strategy has been developed to produce diverse α-functionalized amides from readily and generally available ynamides. An efficient zinc­(II)-catalyzed oxidative azidation and thiocyanation has been achieved, providing facile access to synthetically useful α-azido amides and α-thiocyanate amides, respectively. This chemistry can also be extended to oxidative halogenations by employing the 2-halopyridine N-oxide as both the oxidant and the halogen source, and its mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(12 citation statements)
references
References 138 publications
0
12
0
Order By: Relevance
“…Although a gold-catalyzed formal oxidative Cl–H insertion of α-oxo gold carbenes was first reported by L. Zhang and co-workers and a zinc-catalyzed formal oxidative X–H insertion via S N 2 ′ pathway was later realized by Ye and co-workers, , the direct oxidative F–H insertion of α-oxo gold carbenes was not disclosed until 2016 by Xu and co-workers . As described in Scheme , the treatment of terminal alkynes 321 with hydrogen fluoride (HF) in the presence of 5 mol % JohnPhosAuNTf 2 as the catalyst and 1.4 equiv of N- oxide as the oxidant in DCM could lead to the effective formation of a series of valuable α-fluoroketones 322 in 75–99% yields with broad substrate scope and good functional-group tolerance.…”
Section: Gold-catalyzed Carbene-transfer Reactions Based On Pyridine ...mentioning
confidence: 99%
“…Although a gold-catalyzed formal oxidative Cl–H insertion of α-oxo gold carbenes was first reported by L. Zhang and co-workers and a zinc-catalyzed formal oxidative X–H insertion via S N 2 ′ pathway was later realized by Ye and co-workers, , the direct oxidative F–H insertion of α-oxo gold carbenes was not disclosed until 2016 by Xu and co-workers . As described in Scheme , the treatment of terminal alkynes 321 with hydrogen fluoride (HF) in the presence of 5 mol % JohnPhosAuNTf 2 as the catalyst and 1.4 equiv of N- oxide as the oxidant in DCM could lead to the effective formation of a series of valuable α-fluoroketones 322 in 75–99% yields with broad substrate scope and good functional-group tolerance.…”
Section: Gold-catalyzed Carbene-transfer Reactions Based On Pyridine ...mentioning
confidence: 99%
“…Depending on the nature of the nucleophile, as well as the functional groups of the ynamides, various structurally different products can be formed. With oxygen nucleophiles various reactions can be performed, such as hydration of the ynamide, which can be achieved under acidic conditions to produce functionalized amides Skrydstrup and co‐workers even reported a gold‐catalyzed hydration of dimerized ynamides leading to the formation of 2,5‐diamidofurans . Subsequent to a report by Lam and co‐workers on palladium‐catalyzed hydroacyloxylation of ynamides, it was demonstrated that the addition of carboxylic acids could be performed without catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the generation of a-imino gold carbenes [14][15][16][17][18][19][20][21][22] through gold-catalyzed alkyne amination has gained significant attention, because this strategy offers easy access to a variety of valuable complex nitrogen-containing molecules [23][24][25][26][27][28][29][30][31][32][33]. In our recent study on the ynamide chemistry [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], we first disclosed that benzyl azides could serve as efficient nitrene transfer reagents to react with ynamides for the intermolecular generation of aimino gold carbenes. As a result, this chemistry has evolved into a robust and reliable method for the construction of versatile 2aminoindoles and 3-amino-b-carbolines (Scheme 2a) [49].…”
Section: Introductionmentioning
confidence: 99%